A novel cryo-embedding method for in-depth analysis of craniofacial mini pig bone specimens - Tichá, Pavla; Pilawski, Igor; Yuan, Xue; Pan, Jie; Tulu, Ustun S; Coyac, Benjamin R; Hoffmann, Waldemar; Helms, Jill A (Scientific reports, 2020)
The disconnect between preclinical and clinical results underscores the imperative for establishing good animal models, then gleaning all available data on efficacy, safety, and potential toxicities associated with a device or drug. Mini pigs are a commonly used animal model for testing orthopedic and dental devices because their skeletons are large enough to accommodate human-sized implants. The challenge comes with the analyses of their hard tissues: current methods are time-consuming, destructive, and largely limited to histological observations made from the analysis of very few tissue sections. We developed and employed cryo-based methods that preserved the microarchitecture and the cellular/molecular integrity of mini pig hard tissues, then demonstrated that the results of these histological, histochemical, immunohistochemical, and dynamic histomorphometric analyses e.g., mineral apposition rates were comparable with similar data from preclinical rodent models. Thus, the ability to assess static and dynamic bone states increases the translational value of mini pig and other large animal model studies. In sum, this method represents logical means to minimize the number of animals in a study while simultaneously maximizing the amount of information collected from each specimen.
Keywords: Animals; Cryoultramicrotomy; Cryopreservation; Swine, Miniature; Specimen Handling; Calcification, Physiologic; kryoultramikrotomie; Sucrose; Polyethylene Glycols; Carboxymethylcellulose Sodium; fyziologická kalcifikace; miniaturní prasata; sodná sůl karboxymethylcelulosy; prasata; remodelace kosti; kryoprezervace; polyethylenglykoly; Skull; Male; Swine; Bone Remodeling; lebka; zvířata; mužské pohlaví; odběr biologického vzorku; sacharosa